WAJAH KERAHIMAN ALLAH DALAM PERJANJIAN LAMA - Agustinus Supriyadi (Bahasa Indonesia, 2018)
The theme is taken for this Jubilee is "Compassionate like God - Like the Merciful Father" (Lk 6:36).God is essentially show mercy, even declared himself the Almighty through His mercy. We must realize that God's mercy was not a sign of weakness, but a sign of power. Since the Old Testament, God invites each individual to reflect on his mercy, as proclaimed by the prophet Zephaniah. God has to get rid of the punishment that fell upon His people (Zephaniah 3:15). God is also present in the midst of His people (Zephaniah 3:17) expressed his compassion and solidarity. Moreover, God refurbish the people with His love (Zephaniah 3:17). God's mercy is transformed and entered into the history of mankind, in the person of Jesus Christ. He is the perfect face of God's mercy. Finally, everyone is called to show the face of the compassion of God through everyday life. God's love is so great that it revealed first of the works of creation. His love for man revealed in action by creating the universe and it is all provided for humans. Because after all there (the earth and its contents) God created man in the image of Himself.